2020
DOI: 10.3390/jrfm13090214
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure and Firm Performance in Australian Service Sector Firms: A Panel Data Analysis

Abstract: Using cross-sectional panel data over eleven years (2009–2019), or 1001 firm-year observations, this study examines the relationship between capital structure and firm performance of service sector firms from Australian stock market. Unlike other studies, in this study directional causalities of all performance measures were used to identify the cause of firm performance. The study finds that long-term debt dominates debt choices of Australian service sector companies. Although the finding is to some extent si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 52 publications
(50 reference statements)
1
18
2
1
Order By: Relevance
“…These results are not in line with previous research, which states that the Current Ratio has a significant effect on Return on Assets (E. Damayanti & Chaeruddin, 2021), (Zaman, 2021), (Zarkasy et al, 2021), (Angelina, 2020), (Samo & Murad, 2019), (Ahmed & Bhuyan, 2020). These results align with previous research, which states that the Current Ratio has no effecton Return on Assets (Hutagaol & Sinabutar, 2021;N.O.…”
Section: Effect Of Current Ratio On Roa Of Plantation Sub-sector Comp...contrasting
confidence: 65%
“…These results are not in line with previous research, which states that the Current Ratio has a significant effect on Return on Assets (E. Damayanti & Chaeruddin, 2021), (Zaman, 2021), (Zarkasy et al, 2021), (Angelina, 2020), (Samo & Murad, 2019), (Ahmed & Bhuyan, 2020). These results align with previous research, which states that the Current Ratio has no effecton Return on Assets (Hutagaol & Sinabutar, 2021;N.O.…”
Section: Effect Of Current Ratio On Roa Of Plantation Sub-sector Comp...contrasting
confidence: 65%
“…Companies' performance has suffered because of their usage of debt, as debt has increased interest costs and lowered income (Aziz and Abbas, 2019). However, this result is incongruent with the finding of Ahmed and Bhuyan (2020) which they found that long-term debt to total assets has positively significant relationship with return on equity. From 2009 to 2019, they determined that a high degree of long-term debt in the capital structure is favorable to boosting shareholder value in the case of service sector companies in Australia.…”
Section: Effect Of Capital Structure On Roecontrasting
confidence: 77%
“…The findings support by Zrar et al (2017) that there is a substantial and positive link between tangible assets and Return on Asset (ROA) as a performance measure. A research by Ahmed & Bhuyan, (2020), found a positive link between tangible assets and return on assets (ROA), which validated this conclusion. Thus, the debt-to-equity (DTE) ratio has a positive and substantial relationship with the company's return on asset (ROA).…”
Section: Theoretical Frameworkmentioning
confidence: 57%